2017
DOI: 10.1016/j.ijrobp.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cortex Regions Selectively Vulnerable to Radiation Dose-Dependent Atrophy

Abstract: Purpose/Objectives Neurologic deficits after brain radiotherapy (RT) typically involve decline in higher-order cognitive functions such as attention and memory rather than sensory defects or paralysis. We sought to determine whether areas of cortex critical to cognition are selectively vulnerable to radiation dose-dependent atrophy. Materials/Methods We measured change in cortical thickness in 54 primary brain tumor patients who underwent fractionated, partial brain RT. Study patients had high-resolution, vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…Interestingly, we do observe a decrease in cortical MAP2 and PSD95 staining, which could indicate brain region-specific vulnerability to irradiation, specifically the cortex. In agreement with this, a recent study has shown that in humans cerebral cortical regions are selectively vulnerable to radiation-related atrophy [ 92 ] and a study in rats showed that radiation induces deficits in cortical synaptic plasticity [ 93 ]. Since the spontaneous alternation task relies on various areas of the cortex, as well as the hippocampus, it could be possible that irradiation results in deficits involving the functional integration of these two brain regions.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, we do observe a decrease in cortical MAP2 and PSD95 staining, which could indicate brain region-specific vulnerability to irradiation, specifically the cortex. In agreement with this, a recent study has shown that in humans cerebral cortical regions are selectively vulnerable to radiation-related atrophy [ 92 ] and a study in rats showed that radiation induces deficits in cortical synaptic plasticity [ 93 ]. Since the spontaneous alternation task relies on various areas of the cortex, as well as the hippocampus, it could be possible that irradiation results in deficits involving the functional integration of these two brain regions.…”
Section: Discussionmentioning
confidence: 52%
“…Rather, these new data indicate a cellular response that involves different brain regions at different degrees and rates of changes along the varying post-radiation time points. This differential post-radiation timing is likely due to the intrinsic radiosensitivity to γ-rays in each speci c cerebral region (based, for example, on their intrinsic genetically-determined metabolic rate) as well as possibly related to the total radiation dose administered [39][40][41] . These differential radiosensitivity-related aspects across different brain regions as well as their possible controlled modulation could lead to precise and effective neuroanatomical-based brain radiation protocols selectively tuned for a speci c region of the brain, or a group of disease-related neuroanatomical regions, in the context of a speci c brain disease and local brain tissue vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Cerebral irradiation may cause decline in cognitive function, as described in cohorts of patients receiving radiotherapy for intracranial tumours [10][11][12][13][14][15][16][17][18] and whole brain irradiation [19][20][21]. Different domains of cognitive functions are potentially affected, namely processing speed, attention, working memory, learning and memory, verbal fluency and executive function.…”
Section: Introductionmentioning
confidence: 99%